FACTORS RELATED TO THE SUCCESS OF THE TREATMENT PROGRAM OF MULTIDRUG-RESISTANT TUBERCULOSIS IN POLYCLINIC OF MDR-TB OF THE GENERAL HOSPITAL OF UNDATA PALU, INDONESIA - Napirah, Muhammad Ryman; Wandira, Bertin Ayu; Aulia, Ana (YCAB Publisher & IAKMI SULTRA, 2017)
Background: Incidence of Multi Drug Resistant Tuberculosis remains high in Indonesia. Thus, understanding the factors related to the success of the Government Program on the treatment of Multidrug-resistant is necessity. Objective: This study aims to determine the factors related to the success of government programs on the treatment of MDR-TB patients in Polyclinic of MDR-TB of Undata Palu Hospital.Methods: This was a correlational study with cross-sectional design conducted in the polyclinic of MDR-TB of the General Hospital of Undata Palu from October 2016 to November 2016. There were 46 patients recruited by total sampling. Chi-square was used for data analysis.Results: Findings showed that there were statistically significant correlations between knowledge (p = 0.002), the regularity of treatment (p = 0.000), the role of drug control (p = 0.010), drug side effects (p = 0.000) and quality of service of health workers (p = 0.001) with the success of multidrug-resistant tuberculosis program. There was no correlation between distance to health facilities (p = 0.315) and the success of the treatment.Conclusion: There were significant relationships between knowledge, regularity of treatment, drug control, drug side effects, quality of health staffs and the success of multidrug-resistant tuberculosis program. These factors could be considered important for the government to the success of multidrug-resistant tuberculosis program, especially in the polyclinic of MDR-TB of the General Hospital of Undata Palu.